Penguatan Reformasi Birokrasi Menuju Era Society 5.0 di Indonesia - Andika Yasa; Suswanta Suswanta; M. Rafi; Fajar Rahmanto; Deni Setiawan; Mochammad Iqbal Fadhlurrohman (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
Entering the era of society 5.0, the use of technology has begun to consider the humanities aspects of the problem-solving process in the public sector. Therefore, this study aims to determine the efforts to strengthen bureaucratic reform towards the era of society 5.0 through the governance of human resource development planning by the Ministry of State Apparatus Utilization and Bureaucratic Reform. Then, this study uses qualitative research methods with secondary data collection from previous references such as books, journals, and public documents related to the research focus and analyzed using NVivo12 Plus software with a Cluster Analysis approach. The findings of this study indicate that the Ministry of State Apparatus Utilization and Bureaucratic Reform has strengthened bureaucratic reform through a merit system-based planning governance, where at the stages of recruitment, appointment, and promotion, an examination is carried out on the level of expertise and competence of each apparatus that meets the job requirements while taking into account the aspects of integrity and morality. However, strengthening bureaucratic reform towards the era of society 5.0 in Indonesia has encountered various obstacles related to the still-dominant bureaucratic pathology, a culture of corruption, and the unpreparedness of the bureaucracy for the use of technology and information in the orientation of public services to the community. Therefore, the planning for human resource development by Ministry of State Apparatus Utilization and Bureaucratic Reform in strengthening bureaucratic reform towards the Society 5.0 era must be carried out appropriately by responding to various obstacles that occur as well as all forms of environmental change and development of the times.